Macrophage Heterogeneity in Respiratory Diseases - Carian E. Boorsma; Christina Draijer; Barbro N. Melgert (Mediators of Inflammation)
Macrophages are among the most abundant cells in the respiratory tract, and they can have strikingly different phenotypes within this environment. Our knowledge of the different phenotypes and their functions in the lung is sketchy at best, but they appear to be linked to the protection of gas exchange against microbial threats and excessive tissue responses. Phenotypical changes of macrophages within the lung are found in many respiratory diseases including asthma, chronic obstructive pulmonary disease (COPD), and pulmonary fibrosis. This paper will give an overview of what macrophage phenotypes have been described, what their known functions are, what is known about their presence in the different obstructive and restrictive respiratory diseases (asthma, COPD, pulmonary fibrosis), and how they are thought to contribute to the etiology and resolution of these diseases.